The Effect of Using the Flipped Learning Strategy on Developing Primary Stage Fourth Graders’ English Comprehension Skills in Kuwait - Alshati, Bedour; Al-Khawaldeh, Ahmad Hamad (European Scientific Journal, ESJ, 2023)
This paper focuses on investigating the flipped learning strategy’s effect on developing reading comprehension skills in English among 4thgrade primary pupils in the Kuwaiti capital schools. To achieve the study’s objective, the researcher redesigned 9 reading comprehension lessons from the 4th grade EFL textbook. The researcher used the quasi-experimental approach with an experimental and a control group to measure the effect of the flipped learning strategy on pupils’ achievement in English reading comprehension. To calculate the effect, a post-achievement test was used, and the study sample was intentionally selected. This is consisted of 50 male and female pupils from the basic stage. The data were analyzed statistically, and the results revealed statistically significant differences in favor of the experimental group. Based on the obtained results, the researcher recommended applying the flipped learning strategy in teaching English and related subjects in primary schools in Kuwait and holding training courses for English language teachers to design lessons that align with flipped learning. Further research can address the effect of AI tools in improving reading comprehension.